STRETCHING THE BOUNDARIES: USING ALN TO REACH ON-CAMPUS STUDENTS DURING AN OFF-CAMPUS SUMMER SESSION - Wang, Christine; Kanfer, Alaina; Hinn, Michelle; Arvan, Lanny (Online Learning, 2001)
In this article we study an innovative use of asynchronous learning networks (ALN) to stretch the boundaries of the traditional university campus. An ALN was used to allow traditional on-campus students to take a required course, ECON 300: Intermediate Microeconomic Theory, during summer session while they were off campus, working summer jobs at home. Pre- and post surveys consisting of open-ended and rating scale questions were administered to 29 students. The surveys were used to assess the degree of student satisfaction with various aspects of the online learning experience and their learning environments at home as well as to assess additional important characteristics for successful online learning such as motivation, self-discipline and time management. The results indicate that the transfer from the traditional face-to-face classroom during the academic year to the online summer session requires strong motivation, self-discipline, good time management skills, and a comfortable learning environment including a stable Internet connection. The students’ learning outcomes were closely related to their satisfaction with online communication, technical support, and the course design. Furthermore, prior online class experience affected learning outcomes. Additionally, prior experience with the technologies and a positive attitude toward technology were found to be important for successful online learning. The importance of online course design and student preparation, particularly when traditional on-campus students attend a summer school course through ALN, is discussed.